Use of G3-DHS Bioreactor for Secondary Treatment of Septic Tank Desludging Wastewater - Izarul Machdar; Faisal Faisal; Syaifullah Muhammad; Takashi Onodera; Kazuaki Syutsubo (Waste Technology, 2015)
Study was done for the use of the third-generation of downflow hanging sponge (G3-DHS) bioreactor for secondary treatment of septic tank desludging wastewater. The main objective of this study was to evaluate the prospective system of G3-DHS bioreactor to be applied in Indonesia. During experiment, the G3-DHS bioreactor kept a relatively high dissolved oxygen concentration under natural aeration. At a relatively short hydraulic retention (HRT) of 3 h, the G3-DHS bioreactor could remove up to 21% (SD 15%) of total COD, 21% (SD = 7%) of filtered-COD, 58% (SD = 24%) of unfiltered-BOD, and 33% (SD = 24%) of ammonium removal. The final effluent had an unfiltered-BOD of only 46 mg.L-1 (SD = 20 mg.L-1) that it was below the Indonesian standard (unfiltered-BOD = 100 mg.L-1) for thresholds of domestic wastewater treatment plants effluent.